Mindfulness and Acceptance as Potential Protective Factors for Mothers of Children With Fragile X Syndrome - Wheeler, Anne C.; Miller, Shari; Wylie, Amanda; Edwards, Anne (Frontiers in Public Health, 2018)
Women with an FMR1 premutation may be at increased genetic risk for stress vulnerability. This increased vulnerability, when combined with stressful parenting that can result from raising children with fragile X syndrome (FXS), may result in negative physical and emotional outcomes. Mindfulness and acceptance have been found to be protective factors for parents of children with similar behavioral challenges, but these traits have not previously been explored among mothers with a child with FXS. This study explored the associations of child disability severity with maternal stress, anxiety, depression, and physical health symptoms in 155 biological mothers of children with FXS. Women completed an online survey using standardized measures of stress, mindfulness, and acceptance. General mindfulness, mindfulness in the parenting role, and general acceptance were explored as potential protective factors between the child disability severity and maternal outcomes. Trait mindfulness and acceptance were significant predictors of lower stress, anxiety, depression, and daily health symptoms, while mindful parenting was associated with lower stress, anxiety, and depression. Acceptance was found to attenuate the effects of child severity on maternal stress and depression. These findings suggest that interventions focused on improving mindfulness and acceptance may promote health and well-being for mothers of children with FXS and have important health implications for all individuals with an FMR1 premutation.